The Contemporary Relevance of Serhiy Vynohradsky’s Scientific Heritage - Matselyukh, B.P.; Мацелюх, Б.П. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
On February 24, 2023, we marked the 70th anniversary of the day when the heart of the world-famous microbiologist, one of the founders of general and soil microbiology and ecology, the discoverer of the phenomenon of chemosynthesis in a large variety of autotrophic microorganisms Serhiy Mykolaevych Vynohradsky, stopped beating.